Perbedaan Regulasi Emosi dan Jenis Kelamin pada Mahasiswa yang Bersuku Batak dan Jawa - Widiean Gabriele Yolanda; Y. Bagus Wismanto (Universitas Katolik Soegijapranata, 2017)
This study aims to determine differences of emotion regulation and sex in the Batak ethnic students and Javanese ethnic students. Sampling was conducted using accidental quota sampling. Total subjects in this study were 120 people comprising 60 Batak ethnic students and 60 Javanese ethnic students. Data collection is done by using the scale of emotional regulation in validity test and valid. Data were analyzed using Independent Sample Test. The results show that the difference between the emotion regulation and the Batak ethnic student of Javanese ethnic is significant with results to = -2.355 and p